Variant Interpretation for Dilated Cardiomyopathy: Refinement of the American College of Medical Genetics and Genomics/ClinGen Guidelines for the DCM Precision Medicine Study. (April 2020) - Morales, Ana; Kinnamon, Daniel D.; Jordan, Elizabeth; Platt, Julia; Vatta, Matteo; Dorschner, Michael O.; Starkey, Carl A.; Mead, Jonathan O.; Ai, Tomohiko; Burke, Wylie; Gastier-Foster, Julie; Jarvik, Gail P.; et al.
Abstract : Background: The hypothesis of the Dilated Cardiomyopathy Precision Medicine Study is that most dilated cardiomyopathy has a genetic basis. The study returns results to probands and, when indicated, to relatives. While both the American College of Medical Genetics and Genomics/Association for Molecular Pathology and ClinGen's MYH7 -cardiomyopathy specifications provide relevant guidance for variant interpretation, further gene- and disease-specific considerations were required for dilated cardiomyopathy. To this end, we tailored the ClinGen MYH7 -cardiomyopathy variant interpretation framework; the specifications implemented for the study are presented here. Methods: Modifications were created and approved by an external Variant Adjudication Oversight Committee. After a pilot using 81 probands, further adjustments were made, resulting in 27 criteria (9 modifications of the ClinGen MYH7 framework and reintroduction of 2 American College of Medical Genetics and Genomics/Association of Molecular Pathology criteria that were deemed not applicable by the ClinGen MYH7 working group). Results: These criteria were applied to 2059 variants in a test set of 97 probands. Variants were classified as benign (n=1702), likely benign (n=33), uncertain significance (n=71), likely pathogenic (likely pathogenic; n=12), and pathogenic (P; n=3). Only 2/15 likely pathogenic/P variants were identified in Non-Hispanic African ancestry probands. Conclusions: We tailored the ClinGen MYH7 criteria for our study. Our preliminary data show that 15/97 (15.5%) probands have likely pathogenic/P variants, most of which were identified in probands of Non-Hispanic European ancestry. We anticipate continued evolution of our approach, one that will be informed by new insights on variant interpretation and a greater understanding of the genetic architecture of dilated cardiomyopathy. Clinical Trial Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03037632 Abstract : Supplemental Digital Content is available in the text.